Digital Literacy of Santri Through Islamic Boarding School Culture - Umar, Tia Muthiah; Chaerowati, Dede Lilis; Drajat, Mohamad Subur (KnE Social Sciences, 2023)
This paper examines the digital literacy of santri (students in Islamic boarding schools) developed within the cultural context of pesantren. In the digital era, santri are not only required to possess strong religious knowledge but also life skills to adapt to the rapidly changing times. Therefore, digital literacy in the 4.0 era becomes an essential competence they must acquire. This study explores the phenomenon of santri’s digital literacy fostered by the educational culture established in pesantren. The paper is based on an exploratory study that delves into the topic of digital media culture to varying depths. The findings reveal that the pesantren culture provides a significant opportunity to cultivate a culture of digital media literacy among students. The guidance and direction provided by Islamic boarding schools play a crucial role in strengthening students’ digital attitudes and behaviors, regardless of their location. The commitment of these institutions to developing students’ digital culture is of utmost importance, as the digital era is inevitable. Prohibiting students from engaging with the digital world is not a wise choice; instead, guiding students to develop a discerning and proficient use of digital media in content production can provide a more enriching digital experience within the framework of a digital culture aligned with Islamic values. Keywords: Aisyiyah Boarding School, digital literacy, exploratory study, Islamic boarding school culture